Art as Acting Against the Program of the Apparatus. - Tratnik, Polona (Flusser Studies, 2016)
The article focuses on the role the artist if he or she is not just anyone exhausting the options offered by the program in light of the systems of technical media, and the biotechnological manipulation of the living world, in relation to the issue of programmability as addressed by Vilém Flusser.